2022
DOI: 10.5507/bp.2020.053
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of piritramide in acute postoperative pain - comparison of intramuscular administration with patient-controlled intravenous analgesia and impact of OPRM1 and ABCB1 polymorphisms

Abstract: The aim of this study was to compare the efficacy, consumption and safety after piritramide administered either intramuscularly (IM) on demand or via patient-controlled intravenous analgesia (PCA) and to examine the impact of OPRM1 and ABCB1 gene polymorphisms on the drug efficacy/safety in both regimens. Methods. One hundred and four patients scheduled for elective inguinal hernioplasty received piritramide with PCA or IM for postoperative pain management. We evaluated piritramide consumption, pain intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…As an example, the OPRM1 A118G (rs1799971) allele is the most researched variant in terms of postsurgical pain, with several studies reporting increased pain scores and opioid requirements with the G allele. [10][11][12][13][14][15][16][17][18][19] However, numerous other studies have shown no significant difference between genotypes, [20][21][22][23][24][25][26][27][28][29] with some even reporting an inverse relationship of genotype and postsurgical pain (i.e., the A allele is associated with more postsurgical pain or opioid requirement). 30 Conflicting results such as these confound attempts to create a unified understanding of postsurgical pain genetics.…”
Section: Pain Medicinementioning
confidence: 99%
“…As an example, the OPRM1 A118G (rs1799971) allele is the most researched variant in terms of postsurgical pain, with several studies reporting increased pain scores and opioid requirements with the G allele. [10][11][12][13][14][15][16][17][18][19] However, numerous other studies have shown no significant difference between genotypes, [20][21][22][23][24][25][26][27][28][29] with some even reporting an inverse relationship of genotype and postsurgical pain (i.e., the A allele is associated with more postsurgical pain or opioid requirement). 30 Conflicting results such as these confound attempts to create a unified understanding of postsurgical pain genetics.…”
Section: Pain Medicinementioning
confidence: 99%